2011
DOI: 10.4238/vol10-2gmr1034
|View full text |Cite
|
Sign up to set email alerts
|

β-casein gene expression by in vitro cultured bovine mammary epithelial cells derived from developing mammary glands

Abstract: ABSTRACT. Epithelial cells from mammary gland tissue that are cultured in vitro are able to maintain specific functions of this gland, such as cellular differentiation and milk protein synthesis. These characteristics make these cells a useful model to study mammary gland physiology, development and differentiation; they can also be used for production of exogenous proteins of pharmaceutical interest. Bovine mammary epithelial cells were cultured in vitro after isolation from mammary gland tissue of animals at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Recently, Monzani et al (2011Monzani et al ( , 2013 reported the production of epithelial cell lineages derived from mammary gland expressing the recombinant human coagulation Factor IX (rFIX). The rFIX is an example of recombinant protein of biomedical interest which large-scale production would greatly benefit from bioreactor animals, once its expression and purification from in vitro cell cultures is expensive, and large-scale production is limited.…”
Section: Somatic Cell Nuclear Transfer As the Methods Of Choice For Thmentioning
confidence: 99%
“…Recently, Monzani et al (2011Monzani et al ( , 2013 reported the production of epithelial cell lineages derived from mammary gland expressing the recombinant human coagulation Factor IX (rFIX). The rFIX is an example of recombinant protein of biomedical interest which large-scale production would greatly benefit from bioreactor animals, once its expression and purification from in vitro cell cultures is expensive, and large-scale production is limited.…”
Section: Somatic Cell Nuclear Transfer As the Methods Of Choice For Thmentioning
confidence: 99%
“…All of the constructs produced viral particles that were used to transduce BMECs; the largest construct was approximately 13 kb, which includes the 9.5-kb to be packaged as vector. BMECs were isolated from the mammary gland of a pregnant B. taurus and analyzed for their capacity to differentiate into alveoli-like structures and β-casein expression (Monzani et al, 2011). These cells were used for lentiviral transduction; transgenic cells were selected by antibiotic resistance and hFIX transgene presence was verified by PCR ( Figure 1B).…”
Section: Construction Of Vectors and Transgenic Bmecsmentioning
confidence: 99%
“…BMECs were cultivated on 60-mm dishes to 30% confluence, when cells were transduced by incubation Table 1. Sequence primers used for construction vectors (Monzani et al, 2011).…”
Section: Bmec Transductionmentioning
confidence: 99%
See 2 more Smart Citations